Vocabulary and Grammar Mastery on Students’ Reading Skill - Mildan AF; Nurhayati Nurhayati; Istikomah Istikomah (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2021)
Students’ lack of vocabulary and grammar knowledge can influence their reading skills. This research is aimed at finding the effects of vocabulary and grammar mastery on students’ reading skill. The fourth semester of UNINDRA students in Jakarta were the research participants. The sample was selected through simple random sampling. There were three variables; vocabulary and grammar mastery and English reading skill. Objective tests were administered to the students for the data. Correlation technique and multiple regressions were used for data analysis. The research findings reveal first significant effects of vocabulary and grammar mastery both partially and collectively on the students’ English reading skill, proved by Sig.0.000 < 0.05 and Fo184.710, with correlation coefficient 0.90 and determination coefficient is 0.809 or 80.9%. The regression equation is: Y = 2.071+ 0.529X1 + 0.414X2. It means that the students’ English reading skill is strongly influenced by their vocabulary and grammar mastery. Secondly, there is a significant effect of vocabulary mastery on the reading skill of the fourth semester of UNINDRA students Jakarta, proved with the score of t observed = 5.263 > t table= 1.987and Sig. 0.000 < 0.05. Thirdly, there is a significant effect of grammar mastery on the reading skill of the fourth semester of UNINDRA students Jakarta proved with the score of t observed = 4.514 > t table= 1.987and Sig. 0.000 < 0.05. The conclusion is that there are significant effects of the students’ vocabulary and grammar mastery both partially and collectively on their reading skill.